Pemodelan pada Proses Pengeringan Mekanis Tepung Kasava dengan Menggunakan Pneumatic Dryer: Hubungan Fineness Modulus dengan Variabel Proses Pengeringan - Yus Witdarko; Nursigit Bintoro; Bandul Suratmo; Budi Rahardjo (agriTECH, 2015)
One of the drying methods, which are applied in the industry of flour production, is that pneumatic drying. A wide variety of the variables that are from both of the characteristics of the dried material and drying process condition greatly affect the quality of drying result. Fineness Modulus (FM) and average diameter of flour are important variables in determining the quality of the flour. The objectives of this research was to formulatea mathematical relationship between various pneumatic drying process variables with the fineness modulus of the materials of cassava flour by applying dimensional analysis. In order to realize this goal, pneumatic drying equipment has been designed and tested with a wide variety of treatments such as the input capacity, drying air velocity, particle’s flour diameter, and temperature of air dryer as well.ABSTRAKMetode pengeringan yang diterapkan dalam industri pembuatan tepung salah satunya adalah pneumatic drying. Berbagai macam variabel baik dari sifat-sifat bahan yang dikeringkan maupun kondisi proses pengeringan sangat mempengaruhi kualitas hasil pengeringan. Fineness Modulus (FM) dan diameter tepung rata-rata merupakan variabel-variabel yang penting dalam penentuan kualitas dari tepung. Tujuan dari penelitian ini adalah untuk mencari hubungan matematis antara FM dengan variabel-variabel kondisi proses pengeringan pneumatik. Untuk dapat mewujudkan tujuan tersebut telah dirancang peralatan pneumatic drying dan dilakukan pengujian dengan berbagai macam variasi perlakuan seperti kapasitas input, kecepatan udara pengering, diameter partikel tepung, dan temperatur udara pengering.